Lower Blood Pressure and Gray Matter Integrity Loss in Older Persons. Issue 8 (13th April 2015) - Foster‐Dingley, Jessica C.; Moonen, Justine E.F.; van den Berg‐Huijsmans, Anne A.; de Craen, Anton J.M.; de Ruijter, Wouter; van der Grond, Jeroen; van der Mast, Roos C.
<x xml:space="preserve">Abstract</x> In contrast to middle age, it is unclear whether blood pressure (BP) in older persons is associated with cerebral small vessel disease (cSVD). The authors evaluated the association of BP with signs of cSVD as well as gray and white matter integrity in older persons. In 220 participants aged 75 years and older from the Discontinuation of Antihypertensive Treatment in the Elderly (DANTE) study, cSVD was assessed with conventional magnetic resonance imaging, and microstructural integrity with diffusion tensor and magnetization transfer (MT) imaging. BP measures were not associated with cSVD. However, lower systolic and diastolic BP and mean arterial pressure were associated with decreased gray matter MT ratio peak height and MT ratio in cortical gray matter. Mean arterial pressure was also associated with increased gray matter diffusivity. A lower level of BP was especially associated with worse gray matter integrity. Results suggest that not only upper but preferably lower thresholds of BP values should be observed in older persons.